ALGORITHM FOR CALCULATION OF CLOUD BOTTOM BOUNDARY HEIGHT - R. V. Feodortsau; K. P. Karolik; А. A. Kudriashov (Наука и техника)
The paper considers various methods for determination of parameters included in an equation of laser probing. The parameters have been analyzed in the paper. An algorithm has been developed for determination of cloud bottom boundary height in accordance with the data obtained from a lidar which makes probing with short laser pulses from three atmosphere layers.